Simultaneous nitrification and phosphate removal by bioaugmented aerobic granules treating a fluoroorganic compound - Duque, Anouk F. (2021)
The presence of toxic compounds in wastewater can cause problems for organic matter and nutrient removal. In this study, the long-term effect of a model xenobiotic, 2-fluorophenol (2-FP), on ammonia-oxidizing bacteria (AOB), nitrite oxidizing bacteria (NOB) and phosphate accumulating organisms (PAO) in aerobic granular sludge was investigated. Phosphate (P) and ammonium (N) removal efficiencies were high (>93%) and, after bioaugmentation with 2-FP degrading strain FP1, 2-FP was completely degraded. Neither N nor P removal were affected by 50 mg L−1 of 2-FP in the feed stream. Changes in the aerobic granule bacterial communities were followed. Numerical analysis of the denaturing gradient gel electrophoresis (DGGE) profiles showed low diversity for the ammonia monooxygenase (amoA) gene with an even distribution of species. PAOs, including denitrifying PAO (dPAO), and AOB were present in the 2-FP degrading granules, although dPAO population decreased throughout the 444 days reactor operation. The results demonstrated that the aerobic granules bioaugmented with FP1 strain successfully removed N, P and 2-FP simultaneously.